Towards the use of genetic programming in the ecological modelling of mosquito population dynamics - Azzali, Irene (2022)
Azzali, I., Vanneschi, L., Mosca, A., Bertolotti, L., & Giacobini, M. (2020). Towards the use of genetic programming in the ecological modelling of mosquito population dynamics. Genetic Programming And Evolvable Machines. https://doi.org/10.1007/s10710-019-09374-0